Hak Waris Anak Dari Ibu Pengganti (Surrogate Mother) Ditinjau Dari Hukum Islam - Sukur, Ahmaf Fuzail; Latupono, Barzah; Angga, La Ode (Faculty of Law, Universitas Pattimura, 2024)
Introduction: According to Article 832 of the Civil Code, it is known that legal and illegitimate blood and the spouse with the longest life are entitled as heirs. Islamic Sharia establishes the rules of inheritance in an orderly and fair manner. When a person, male or female, is legally assigned to possess. Islam also provides for the right to transfer one's property after death to his heirs and all his relatives, without distinguishing between male and female.Purposes of the Research: The purpose of this study is to know and explain the legal position of children from surrogate mothers in terms of Islamic Law. 1). To know and explain the inheritance rights of children from surrogate mothers in terms of Islamic Law. 2). As one of the academic requirements to obtain a law degree at the Faculty of Law, Pattimura University.Methods of the Research: This research uses a type of normative juridical research that is analytical descriptive.Results of the Research: 1. The legal status of surrogate mothers in Islamic law is that in Islamic law, a child born to a surrogate mother belongs to the mother who conceived and gave birth to the child, even though the egg is not hers. Children born through this process are also assigned to pregnant and giving birth mothers, that is, mothers whose womb is rented out. A child born with surrogacy cannot be combined with a woman who has a mother egg or embryo in the child, because according to Islamic law, surrogacy is not permissible or haram. 2. The right of inheritance of the surrogate mother's child in the sense of Islamic law is the right of inheritance of a child born to a surrogate mother, because in the Qur'an it is explained that the woman who gives birth and the pregnant woman has the right to take care of her, because in the blood of the child flows the blood of the woman who contains her.